﻿Share the care SG : supporting family-caregivers of persons with special needs - Ho, Xiu Xian (2016)
Share the Care SG is the first local campaign calling for community support for family- caregivers of persons with special needs. Led by four final-year undergraduates from the Wee Kim Wee School of Communication and Information at the Nanyang Technological University (NTU), Share the Care SG is a public will campaign that encourages Singaporeans to “care for family-caregivers” of persons with special needs by providing social support. Share the Care SG targeted adults aged 25 to 54 years old, activating them to offer social support to the family-caregivers around them. By raising awareness of the challenges faced by family-caregivers and the ways one can offer social support, the campaign aims to cultivate an inclusive environment where members in the community offer support to the family-caregivers among them. This report presents the findings from primary and secondary research which helped shape the campaign’s goal, objectives and strategies. Subsequent sections detail the campaign’s progress from conceptualisation to execution. Lastly, success of the campaign was evaluated, with a discussion on its effectiveness and limitations. Recommendations were also made to help guide future projects of a similar nature. This report is accompanied by an appendix containing campaign materials including diagrams and collateral designs for reference to the main report.